Adaptation by Men to the Nurse Role. "Being Craftsmen in the Construction of their Professional Trajectory" - Velásquez Vergara, Sandra Milena; Moreno Fergusson, María Elisa; Arroyave Álvarez, Edgar Orlando; Cacante Caballero, Jasmín Viviana (Investigación y Educación en Enfermería, 2023)
Objective. This work sought to describe the adaptation process by men to the nurse role. Methods. Secondary analysis of data from a collective case study that had as participants 12 male nurses working in the city of Medellín, with ages between 28 and 47 years and average time of professional experience of 11 years. Information collection was carried out through in-depth interviews. The analysis was conducted through Roy’s Adaptation Model (RAM), reading of the interviews, identification of RAM’s components, grouping of fragments, assignment of tags, construction of a matrix and classification. Results. The analysis performed accounts for the coping processes and adaptation by male nurses and the ineffective responses (control of emotions and emotional silencing) when practicing a role considered feminine. Conclusion. In this study, it was possible to establish that, to achieve adaptation within nursing, men use strategies related with changes in bodily appearance, management of physical strength, and management of emotions.